2009
DOI: 10.1007/s00572-009-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal status of plant species in the Chaco Serrano Woodland from central Argentina

Abstract: We examined the mycorrhizal type of 128 plant species in two patches of native vegetation of the Chaco Serrano Woodland, central Argentina, the largest dry forest area in South America. Of the 128 plant species investigated (belonging to 111 genera in 53 families), 114 were colonized by arbuscular mycorrhizal fungi (AM), orchid mycorrhizal associations were present in the five terrestrial orchid species analyzed, one ectomycorrhiza was only present in Salix humboldtiana Willd., and 96 harbored a dark septate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
7
15
1
2
Order By: Relevance
“…Akond et al (2008) also reported low incidence of mycorrhizal associations (36%) in Solanaceae vegetable crop plants from Bangladesh. The moderate mean level of AM fungal colonization (69%) observed in the present study is consistent with findings from Muthukumar and Udaiyan (2000), Muthukumar et al (2006) and Fracchia et al (2009) for mean AM colonization levels in solanaceous plant species: 54% in material from the Western Ghats, and 70% in material from the Chacco Serrano Woodland, central Argentina. We found that Solanum melongena had 71% of its root length colonized by AM fungi, whereas Akond et al (2008) reported a much lower colonization level (38%) for the same species.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Akond et al (2008) also reported low incidence of mycorrhizal associations (36%) in Solanaceae vegetable crop plants from Bangladesh. The moderate mean level of AM fungal colonization (69%) observed in the present study is consistent with findings from Muthukumar and Udaiyan (2000), Muthukumar et al (2006) and Fracchia et al (2009) for mean AM colonization levels in solanaceous plant species: 54% in material from the Western Ghats, and 70% in material from the Chacco Serrano Woodland, central Argentina. We found that Solanum melongena had 71% of its root length colonized by AM fungi, whereas Akond et al (2008) reported a much lower colonization level (38%) for the same species.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, 8 (40%) of the 20 plant species had Paris-type AM morphology, higher than the 15% reported for members of this family by Dickson et al (2007). Our finding of the absence of typical Arum-type morphology in this family contrasts with findings from Fracchia et al (2009), who reported Arum-type AM morphology in 2 of the 8 taxa they examined. Intermediatetype morphology was dominant (present in 14 of our 20 species), which is in line with findings by Muthukumar and Tamilselvi (2010): 75% of the solanaceous crop species they examined had intermediate-type AM morphology.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Rhizosphere soil and whole orchid plants were collected from Huerta Grande, Villa Giardino, La Falda and Capilla del Monte at the Valle de Punilla in Córdoba Province. The samples were kept in plastic bags and later processed within 48h (Fracchia et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…In Africa, Acacia s. l. are ectomycorrhizal associated with gasteroid and telephoroid Basidiomycota (Diédhiou et al 2005;Sprent and James 2007). In Argentina, species of Acacia s. l. and Prosopis were reported as being arbuscular mycorrhizal (Fracchia et al 2009) in Córdoba Province; however, other A C B species of these genera are cited as ectomycorrhizal in South America (Frioni et al 1999). Thus, in Argentina, ectomycorrhizal fungi, potentially including B. congregata, could establish ectomycorrhizae with Prosopis at different developmental stages than those studied by Fracchia et al (2009), considering that this type of association may be transient over the life cycle of the host.…”
Section: Semmentioning
confidence: 99%